Respostas termorreguladoras e ambiente térmico de bovinos leiteiros em regiões de clima tropical - Alves, Melânia de Araújo (2014)
Several environmental factors can cause stress to cattle. Among these factors, climatic variations have gained much attention in tropical regions. In the dry season, water shortages in some regions affect food production, which increases the cost of production. However, in the rainy season, high relative humidity combined with high temperatures and the large accumulation of mud on the facilities impairs heat loss by evaporation and increases the incidence of mastitis. Therefore, the objective was to evaluate thermoregulatory responses and thermal environment for the creation of crossbred dairy cows in the state of Ceará during the rainy season. The study was conducted on a commercial farm in Beberibe – CE - Brazil, between the months of February and May 2013. 16 crossbred heifers (Bos taurus x Bos indicus) were evaluated. Environmental variables: air temperature (AT) and relative humidity (RH) were measured; physiological variables: rectal temperature (RT) , respiratory rate (RR) , skin surface temperature (ST) and skin temperature of the udder of animals healthy and presenting clinical mastitis, behavioral variables, and milk production; Temperature and Humidity Index (THI) and Enthalpy Comfort Index (ECI) were calculated. The average values of AT were in the comfort range. The RH was above 75 %, which may be due to the large accumulation of mud on the facility. The average values of THI expressed danger and the ECI indicated a comfortable situation in the morning and an alert situation in the evening. The average values of RT, ST and RR were in the range considered optimal, which may indicate high adaptability of these animals. Behaviors showed great influence of farm management and not the environment, only the frequency of permanence in places with mud varied. In the months when rainfall was higher, the frequency was higher and on days when the temperatures inside the facility were higher at 29 º C, the frequency of this behavior was also higher, which may indicate the animals sought places more conducive to heat exchange. Milk production was not affected by environmental conditions.